2020
DOI: 10.1002/smll.201905422
|View full text |Cite
|
Sign up to set email alerts
|

Surface Roughness Gradients Reveal Topography‐Specific Mechanosensitive Responses in Human Mesenchymal Stem Cells

Abstract: The topographic features of an implant, which mechanically regulate cell behaviors and functions, are critical for the clinical success in tissue regeneration. How cells sense and respond to the topographical cues, e.g., interfacial roughness, is yet to be fully understood and even debatable. Here, the mechanotransduction and fate determination of human mesenchymal stem cells (MSCs) on surface roughness gradients are systematically studied. The broad range of topographical scales and high‐throughput imaging is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
164
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(191 citation statements)
references
References 45 publications
9
164
0
Order By: Relevance
“…It was hypothesized by the authors that such specific Ra values promoting the commitment of BM-MSCs towards the osteogenic lineage, might mimic the pits left by osteoclastic bone resorption. Surface roughness gradients have also been explored onto catecholic polyglycerol coatings, which were the highest formation of FAs and filopodia, as well as the highest cellular tension, was observed for a Ra of 278.64 nm [ 98 ]. Such a Ra value also enhanced the osteogenic differentiation of MSCs.…”
Section: The Effect Of Substrate Topographymentioning
confidence: 99%
See 1 more Smart Citation
“…It was hypothesized by the authors that such specific Ra values promoting the commitment of BM-MSCs towards the osteogenic lineage, might mimic the pits left by osteoclastic bone resorption. Surface roughness gradients have also been explored onto catecholic polyglycerol coatings, which were the highest formation of FAs and filopodia, as well as the highest cellular tension, was observed for a Ra of 278.64 nm [ 98 ]. Such a Ra value also enhanced the osteogenic differentiation of MSCs.…”
Section: The Effect Of Substrate Topographymentioning
confidence: 99%
“…An efficient strategy to improve the biological performance of Ti implants is to implement topographical structures, including roughness. However, the reported studies show substantial discrepancies, a fact that can be attributed to the lack of a high-throughput strategy which could have been achieved by using surface roughness gradients [ 98 ]. For example, a first study conducted in 2009 showed how Ti surfaces with small Ra of 15 nm in height enhanced the adhesion and osteogenesis of MSCs as compared to Ras of 55 and 100 nm [ 103 ].…”
Section: The Effect Of Substrate Topographymentioning
confidence: 99%
“…The mechanical properties of the materials to which cells adhere play a major role in regulating cellular mechanotransduction. [ 1 ] While the mechanisms governing cellular mechanotransduction on materials with static properties, e.g., stiffness, [ 2–4 ] geometry, [ 5 ] topography, [ 6,7 ] or spatial ligand patterning [ 8,9 ] are increasingly characterized, less is known about mechanosensitive cellular response to materials with dynamic properties. In general, actomyosin contractility in response to mechanical stimulation causes enhanced cytoskeletal filament assembly and focal adhesion formation, which in turn result in unfolding of structural “molecular strain gauge” proteins and subsequent activation of mechanosensitive signaling pathways.…”
Section: Figurementioning
confidence: 99%
“…The deployment of gradients allows for exploring the effect of continuously varying surface parameters within a single experiment [ 17 ], with minimized system errors and saved cost. Previous reports have demonstrated the feasibility and advantages of the surface gradient approach in the study of the response of a variety of cells, including endothelial colony-forming cells [ 13 ], MC3T3-E1 osteoblastic cells [ 18 ], and human mesenchymal stem cells [ 19 ]. While methods to fabricate morphological gradients mainly include particle binding, electrochemical etching, erosion/chemical polishing—replica [ 17 ], the substrates used are often limited to silicon or glass with entirely different characteristics from biodegradable materials.…”
Section: Introductionmentioning
confidence: 99%